Cocoa Butter Characteristic on Different Roasting Temperature and Its Final Sensory Profiles - Hendy Firmanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Cocoa butter is an intermediate product of cocoa processing separated from cocoa nibs or cocoa mass. Heat through cocoa processing affect the characteristic of fat including roasting process. The aim of this experiment is to evaluate the characteristic changes and sensory profile of cocoa butter in different operational roasting temperature. This experiment was conducted in Postharvest Laboratory of Indonesian Coffee and Cocoa Research Institute using dry cocoa bean from Glenmore estate in Banyuwangi (G) and from Kaliwining estate in Jember (K) in grade A according to standard of SNI 2323:2008/Amd1:2010 with moisture content of 7.5% originated from Trinitario bean and roasting temperature 120OC (T1) and 150OC (T2). Cocoa butter characteristic evaluated based on yield of separated fat, saponification, free fatty acid, peroxide value, colour and its melting profiles. Flavour description evaluated by sensory test using native panelist. Result shows nosignificant difference between roasting temperature but shows difference in appearance and flavour profile. Yield of separated fat is 35.95% per cocoa mass weight, saponification value is 193.36, free fatty acid is 0.72 and peroxide value 2.96 comply to the national standard of commercial butter. Cocoa butter appearance in T2 shows more intense of red colour than T1. Roasting temperature T1 and T2 enhance the chocolaty and nutty flavour but T2 shows burnt off-flavour for bean of Kaliwining (K). Melting point cocoa butter is 36.63OC and qualified as hard cocoa butter.